MING YINGZONG EARLY WERE CAPTURED BY MONGOLIA MINGMENG ENVOYS BETWEEN RESEARCH (AUGUST-OCTOBER ,1449) - Hang Hui Ling, (Acta Mongolica, 2013)
Ming Yingzong after being captured in Mongolia, Esen Taishi first army called Pro Beijing MingYingzong was captured early. Scholars believe that this period Mingmeng exchange of envoys between two or three times. This article refer to the official repair histories and historical records of private writings and other records, scholars in the past to correct erroneous views, propose this period should be a total of five envoys exchanges.